Surgical Reflection Short Bowel Syndrome Truly Challenging - Amaro, Dianna Estefany Lopez; Pazos, Mauricio Israel Flores; Barrón, Gema Méndez; Carrillo, Carol Atzimba Zepeda; Montiel, Angel Flores; Terrones, Carlos Iván Díaz; Román, Laura Valeria Medina; Sixtos, Jaime Ricardo López; Gómez, Jesús Ricardo Delgado; Ambriz, Iñaki Rubén Montes de Oca; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2024)
.